1990
DOI: 10.1111/j.1432-1033.1990.tb19139.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activation of protein kinase C‐ɛ

Abstract: Proteolysis of native protein kinase C-E (PKC-e) is shown to occur through tryptic attack at multiple sites within the PKC-s V2/V3 domain. Following initial cleavage of PKC-s with trypsin, the kinase activity using a synthetic peptide substrate was found to be lipid/phorbol-ester independent, as observed for other members of this kinase family. Interestingly, there is also an increase in the histone kinase activity, indicating that there is an influence of the regulatory domain of the enzyme on substrate speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 16 publications
7
71
0
Order By: Relevance
“…A comparable pattern has been observed with PKC-␦ phosphorylation of the ␥ chain of the IgE receptor, where the rate of threonine phosphorylation was increased 2.5-fold using PI compared with PS, whereas the effect of PG was not tested (53). PKC-⑀ displays PG-stimulable activity toward a PKC-⑀ synthetic peptide resembling the PKC-⑀ pseudosubstrate site, with a serine residue at the alanine position (54). PKC-⑀ was also found to phosphorylate histones poorly, similar to the present findings with PKC-.…”
Section: Discussionsupporting
confidence: 77%
“…A comparable pattern has been observed with PKC-␦ phosphorylation of the ␥ chain of the IgE receptor, where the rate of threonine phosphorylation was increased 2.5-fold using PI compared with PS, whereas the effect of PG was not tested (53). PKC-⑀ displays PG-stimulable activity toward a PKC-⑀ synthetic peptide resembling the PKC-⑀ pseudosubstrate site, with a serine residue at the alanine position (54). PKC-⑀ was also found to phosphorylate histones poorly, similar to the present findings with PKC-.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore the catalytically active fragment of PKC-6 will phosphorylate histone 111s (see Fig. 2) implying that like PKC-E there is an influence on specificity determined by the regulatory domain [17,181. It is likely that the form of PKC-6 previously detected following expression in COS-1 cells was the proteolysed catalytic fragment [8].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the synthetic peptide based on the PKCa pseudosubstrate site (peptide-a [4]), PKC-6 shows some differences with respect to PKC-a, PI [3]. Interestingly the synthetic peptide based on the PKC-6 pseudosubstrate site (peptide-6) has a Vm,,/Km value of 153 for PKC-6 and this reflects a significantly lower apparent K, (3.5 pM); PKC-E likewise shows a low apparent K, (8 pM) for this substrate (A. R. Olivier, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic activation and degradation of PKC isozymes has been widely discussed as a physiological mechanism to regulate the activity and localization of PKC isozymes. Tryptic activation of PKCe increased the kinase activity towards histone about 10-fold [49], Also, Suzuki et al [50] have shown that PKCfl and PKCy isozymes are selectively associated with postsynaptic densities obtained from rat hippocampus and suggest that proteolytic activation of these isozymes could be a step in postsynaptic signal processing. It may be therefore possible that PKCfl and PKCy present in hippocampal neurones in culture are subject to specific regulation by in vivo proteolysis.…”
Section: Phase Contrastmentioning
confidence: 99%